Health-related quality of life in a randomized trial of neoadjuvant chemotherapy or chemoradiotherapy plus surgery in patients with oesophageal cancer (NeoRes trial). Issue 11 (22nd August 2019) - Sunde, B; Klevebro, F; Johar, A; Johnsen, G; Jacobsen, A-B; Glenjen, N I; Friesland, S; Lindblad, M; Ajengui, A; Lundell, L; Lagergren, P; Nilsson, M
Abstract: Background: There are few data comparing health-related quality of life (HRQoL) after neoadjuvant chemotherapy alone (nCT) compared with neoadjuvant chemoradiotherapy (nCRT) in patients with oesophageal cancer. Methods: In the NeoRes trial, patients were assigned randomly in a 1 : 1 ratio to receive either cisplatin 100 mg/m 2 on day 1 and an infusion of 750 mg per m 2 5-fluorouracil over 24 h on days 1–5 in three 21-day cycles (nCT) or the same chemotherapy regimen, but with the addition of 40 Gy radiotherapy (nCRT). HRQoL data were collected at baseline, after neoadjuvant therapy and at 1, 3 and 5 years after surgery. The European Organisation for Research and Treatment of Cancer (EORTC) core questionnaire QLQ-C30 and disease-specific modules were used. Results: Of 181 patients randomized, 165 were included in the analysis of HRQoL. In a direct comparison between the allocated treatments, odynophagia after completion of neoadjuvant therapy but before surgery ( P = 0·047) and troublesome coughing at 3 years' follow-up ( P = 0·011) were more pronounced in the nCRT arm. In the longitudinal analyses within each treatment arm, a large deterioration in HRQoL was noted at 1 year. Some recovery was seen in both arms over time but, after 3 and 5 years, patients in the nCRT arm reported more symptoms compared with baseline than patients in the nCT arm. Conclusion: HRQoL after multimodal treatment for cancer of the oesophagus or gastro-oesophageal junction was impaired and more pronounced in patients who underwent nCRT, with only partial recovery over time. Graphical Abstract: Analysis of health-related quality of life in the NeoRes trial found that patients allocated to neoadjuvant chemoradiotherapy (nCRT) reported more symptoms at 3 and 5 years' follow-up compared with those who had neoadjuvant chemotherapy (nCT) for oespophageal cancer. More impairment after chemoradiation